2011
DOI: 10.3109/15563650.2011.624100
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and analytical features of severe suicidal quetiapine overdoses – a retrospective cohort study

Abstract: In this study, quetiapine overdoses were associated with significant toxicity and a fairly high number of complications. A careful and often prolonged clinical observation in the more severe cases of overdose seems mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 35 publications
1
21
1
3
Order By: Relevance
“…In a study of fatalities documented in postmarketing safety reports, Marder et al (43) found the frequency of respiratory effects was second only to cardiovascular effects for olanzapine. Two other reports found quetiapine to be associated with respiratory depression in severe cases (44,45). The following drugs included in this report were associated with at least 200 serious outcomes and with frequencies of respiratory depression .6%: doxepin (13.6%), amitriptyline (12.1%), pregabalin (11.3%), benzodiazepines (11.2%), imipramine (9.0%), quetiapine (8.0%), olanzapine (7.6%), and gabapentin (7.3%).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of fatalities documented in postmarketing safety reports, Marder et al (43) found the frequency of respiratory effects was second only to cardiovascular effects for olanzapine. Two other reports found quetiapine to be associated with respiratory depression in severe cases (44,45). The following drugs included in this report were associated with at least 200 serious outcomes and with frequencies of respiratory depression .6%: doxepin (13.6%), amitriptyline (12.1%), pregabalin (11.3%), benzodiazepines (11.2%), imipramine (9.0%), quetiapine (8.0%), olanzapine (7.6%), and gabapentin (7.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Manche Patienten weisen ein anticholinerges Syndrom auf, das auf Physostigmin anspricht. Bei verlängerter QT-Zeit muss von einer Kardiotoxizität ausgegangen werden [14]. Eine besondere Gefahr geht von den Retardpräparaten aus mit über Tage ansteigenden Serumspiegeln.…”
Section: Vergiftungen Durch Quetiapin ▼unclassified
“…Manche Patienten weisen ein anticholinerges Syndrom auf, das auf Physostigmin anspricht. Bei verlängerter QT-Zeit muss von einer Kardiotoxizität ausgegangen werden [26]. Eine besondere Gefahr geht von den Retardpräparaten aus mit über Tage ansteigenden Serumspiegeln.…”
Section: Vergiftungen Durch Quetiapinunclassified